Analisis Kapasitas Saluran Drainase Di Jl. Kartini Kecamatan Tanjung Karang Pusat Kota Bandar Lampung - Maulana, Sugeng Haris; Sumiharni, Sumiharni; Purwadi, Ofik Taufik; Mariyanto, Mariyanto (Universitas Lampung, 2023)
The Bandar Lampung area which is quite routinely hit by floods is in Tanjung Karang Pusat District, the Jl. Wolter Monginsidi to Jl. Kartini. The reason is the high rainfall, as well as the curved road conditions and the performance of the drainage channel that is not optimal enough to accommodate the water discharge before carrying it to the Way Awi river which is on the road. The option that can be taken to reduce the risk of flooding is by evaluating the drainage channels on the road, taking into account the capacity of the drainage channels so that they are able to accommodate the flood discharge through them. The design discharge is calculated using hydrological analysis, rational methods, and based on maximum rainfall data for the last 10 years. For channel discharge capacity is calculated using hydraulics analysis and Manning's formula. The results of the analysis of the existing discharge capacity in most of the drainage channel segments are still able to accommodate the planned discharge with a 5-year return period of rain, so there is no need to increase the dimensions, except for segment 4, because the existing drainage capacity (Qs) is 0.700 m3/s smaller than design discharge (Qr) 1,238 m3/s. These conditions require the need to increase the dimensions of the drainage channel in order to accommodate the discharge through it. Key words : drainage, hydrological analysis, hydraulic analysis, flooding.